Civic Media Literacies Re-Imagining Human Connection in an Age of Digital Abundance - Mihailidis, Paul (2018)
Civic life today is mediated. Communities small and large are now using connective platforms to share information, engage in local issues, facilitate vibrant debate, and advocate for social causes. In this timely book, Paul Mihailidisexplores the texture of daily engagement in civic life, and the resources-human, technological, and practical-that citizens employ when engaging in civic actions for positive social impact. In addition to examining the daily civic actions that are embedded in media and digital literacies and human connectedness, Mihailidis outlines a model for empowering young citizens to use media to meaningfully engage in daily life.